Multi-scale analysis of the interaction in ultra-long carbon nanotubes and bundles. (September 2020) - Liu, Mengxiong; Ye, Xuan; Bai, Yunxiang; Zhang, Rufan; Wei, Fei; Li, Xide
Highlights: The inter-wall/inter-tube interaction in double-walled carbon nanotube (DWCNT)/carbon nanotube bundle (CNTB) is firstly in-situ measured under optical microscope. The multi-scale model, where the dynamic friction is included specially, is developed to illustrate the interaction in the ultra-long DWCNT/CNTB. The force to pull out the inner/core tube consists of three parts, including the boundary effect, the configuration force and the dynamic friction. Results from the multi-scale model are verified by the atomic simulation and can explain the physical mechanism behind the experimental phenomena. Abstract: Ultralow inter-wall interaction is realized in centimeter-long double-walled carbon nanotube (DWCNT) (Zhang, R. et al. Nat. Nanotech. 8, 912-916 (2013)). To further illustrate the mechanism of this special phenomenon, theoretical analysis combining with the experimental test is conducted, where study of the inter-tube interaction in the carbon nanotube bundles (CNTBs) is also included in this paper. In experiment, nanomanipulation difficulties of the ultra-long carbon nanotube (CNT)/CNTB is overcome by establishing a micro/nanoscale mechanical testing system (m/n-MTS), based on which the inter-wall/inter-tube interaction is firstly in-situ measured under optical microscope (OM). In theory, according to the bottom-up approach, a multi-scale model is developed specially, by which results obtained can be directly compared with the experimental data. The pull-out force consists of three parts: the boundary effect, the configuration force and the dynamic friction. The boundary effect can account for more than 70% when the pull-out velocity equals to 1 μm/s. The configuration force is greatly enhanced for the CNTB because of the commensurate configuration in the circumferential direction. The dynamic friction shows linear dependence on the pull-out velocity and relates to the overlapped area, which can be manifested when the pull-out velocity reaches to a dozen μm/s for the ultra-long DWCNT. The dynamic friction coefficient is proved to be 0.29 multiple of critical value based on the experiment data. The pull-out force in the CNTB is found far less than that in the DWCNT due to the greatly reduced contact area. Moreover, it can be deduced that the dynamic friction will show the same order of magnitude as the contribution from the boundary when the pull-out velocity equals to 10 μm/s or the length is 10 mm. This research reveals the underlying mechanism of the interaction, especially for the dynamic friction force exhibited in the ultra-long CNT/CNTB, and can provide help for designing devices with ultralow friction on macroscale. Graphical abstract: Image, graphical abstract